Non lethal tools to assess the toxicological hazard of endocrine disruptor organochlorine contaminants in mediterranean cetaceans - Fossi, M. C.; Marsili, L. (2004)
The Mediterranean top predators, and particularly cetacean odontocetes, accumulate high concentrations of organochlorine contaminants (OCs), incurring high toxicological risk. Some organochlorine compounds, now with worldwide distribution, are known as endocrine disrupting chemicals (EDCs). Here the hypothesis that some Mediterranean cetaceans (Stenella coeruleoalba, Delphinus delphis, Tursiops truncatus and Balaenoptera physalus) are potentially at risk due to organochlorines with endocrine disrupting capacity is investigated. As “diagnostic” tool we use benzo(a)pyrene monooxygenase (CYP1A1) activity in marine mammal skin biopsies (non-lethal biomarker) as a potential indicator of exposure to organochlorines, with special reference to the compounds with endocrine disrupting capacity. A statistically significant correlation was found between BPMO activity and organochlorine EDs levels in skin biopsies of males of Balaenoptera physalus. A statistical correlation was also found between BPMO activity and DDT levels in skin biopsies of the endangered Mediterranean population of Delphinus delphis. As “prognostic” tool we propose the immunofluorescence technique in fibroblast cell cultures, for a qualitative and quantitative evaluation of the target proteins as CYP450 1A1-1A2, CYP450 2B4 and estrogen receptor (ER).